Nursing interventions and outcomes for pressure ulcer risk in critically ill patients - Luana Nunes Caldini; Renan Alves Silva; Geórgia Alcântara Alencar Melo; Francisco Gilberto Fernandes Pereira; Natasha Marques Frota; Joselany Áfio Caetano (Rev Rene)
Objective: to establish relationships between nursing interventions and outcomes for the diagnosis Pressure ulcer risk in critically ill patients. Methods: longitudinal study of 63 patients in an intensive care unit. An instrument with clinical data of patients and the Braden Scale were used. The cross-mapping technique was used to establish the nursing interventions and outcomes for each risk factor. Results: four intervention/outcome relationships were found for sensory perception; 11 for moisture; five for activity; six for nutrition; four for mobility; and three for friction/shear. Conclusion: thirty-three relationships related to the observed risk factors were found, with higher frequency of moisture. The relationships found with moisture were: urinary elimination, response to medication, wound healing: secondary intention, self-care: bathing, fluid, electrolyte and acid-base balance, intestinal continence and tissue integrity: skin and mucous membranes.